RESEPSI PEMBACA TERHADAP KOMIK SI JUKI DI WEBTOON: KAJIAN ESTETIKA RESEPSI GENRE KOMEDI - Alfrendo Nainggolan; Mara Untung Ritonga (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to describe the reader's reception of the Si Juki comic on the webtoon online comic reading application using Hans Robert Jauss's reception aesthetics study. This research method uses a qualitative descriptive method by describing data in the form of comments from readers who provide responses to acceptance, criticism and suggestions in the Si Juki comic on the webtoon. The data collection techniques used are observation techniques and documentation techniques using studies from research as reference material, and using the note-taking technique by concluding data by reading the comic script and responses or comments on the Si Juki comic written by Faza Meonk. The results of this study analyzed 50 reader comments on three Si Juki comic titles uploaded on the Webtoon platform, namely "Si Juki: Lika-Liku Anak Kos", "Si Juki: Kisah Kusut Dunia Dongeng", and "Nostalgia Ramadhan Si Juki Kecil". These comments were collected systematically as primary data containing opinions, assessments, and readers' responses to the storyline, characters, and humorous elements that are characteristic of this comic. The comments collected show a diversity of responses, ranging from comments that emphasize the humorous aspects, to comments that emphasize social satire and criticism of the reality raised in the comic.